Crystallization and optical properties of CCTO thin films under pressure influence - Sequinel, T. [UNESP]; Tebcherani, S. M.; Kubaski, E. T.; Oliveira, L. H.; Li, M. Siu; Varela, J. A. [UNESP]; Laudon, M.; Romanowicz, B. (Crc Press-taylor & Francis Group, 2012)
CCTO thin films were deposited on Pt(111)/Ti/SiO2/Si substrates using a chemical (polymeric precursor) and pressure method. The pressure effects on the CCTO thin films were evaluated by XRD, FEG-SEM and optical properties. Pressure films were found to be more homogeneous and dense than chemical deposition films. Pressure also leaded to an increase in the photoluminescence emission; it is suggested that the displacement of Ti in the titanate clusters, favors the charge transference from TiO6 to [TiO5Voz], TiO5Voz] to [CaO11Voz and [TiO5Voz] to [CuO4](x). The low synthesis temperature used in the pressure method allows the deposition of films on less expensive substrates (i.e. glass, aluminum, polymer and others).
Keywords: CCTO; thin films; pressure method